2011
DOI: 10.1007/s13277-011-0154-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of miR-21, miR-141, and miR-221 in blood circulation of patients with prostate cancer

Abstract: In addition to their potential as tissue-based markers for cancer classification and prognostication, the study of microRNAs (miRNAs) in blood circulation is also of interest. In the present study, we investigated the amounts of three cancer-related miRNAs, miR-21, -141, and -221 in blood plasma of prostate cancer (PCa) patients. A cohort of 51 patients with PCa was enrolled into the study, and miRNAs were measured in two subgroups, with localized/local advanced or metastatic PCa. A group of 20 healthy individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
237
3
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(255 citation statements)
references
References 20 publications
(25 reference statements)
9
237
3
6
Order By: Relevance
“…14 Mitchell et al 8 were the first to describe the overexpression of circulating miR-141 in advanced PCa, and Bryant et al 15 discovered an association of miR-141 with metastatic PCa. In addition, Yaman Agaoglu et al 16 Figure 1 Box plot of different serum miR-141 expression levels in different groups of patients (group 1, BPH patients, n56; group 2, LPC patients, n520; group 3, HNPC patients, n510; group 4, HSPC patients, n510; group 5, HRPC patients, n510). By one-way ANOVA test and independent samples t-test, serum miR-141 expressed higher in the patients with bone metastasis (HNPC, HSPC and HRPC patients) than those in BPH and LPC patients (P,0.001).…”
Section: Discussionmentioning
confidence: 99%
“…14 Mitchell et al 8 were the first to describe the overexpression of circulating miR-141 in advanced PCa, and Bryant et al 15 discovered an association of miR-141 with metastatic PCa. In addition, Yaman Agaoglu et al 16 Figure 1 Box plot of different serum miR-141 expression levels in different groups of patients (group 1, BPH patients, n56; group 2, LPC patients, n520; group 3, HNPC patients, n510; group 4, HSPC patients, n510; group 5, HRPC patients, n510). By one-way ANOVA test and independent samples t-test, serum miR-141 expressed higher in the patients with bone metastasis (HNPC, HSPC and HRPC patients) than those in BPH and LPC patients (P,0.001).…”
Section: Discussionmentioning
confidence: 99%
“…121,126 In nine out of these 15 miR-141-studies, miR-141 was only evaluated as a marker of advanced or metastatic prostate cancer (Table 3). 20,84,96,99,101,103,[113][114][115] but was frequently, if at all reported, not better than the routine marker PSA. 114,115,118 These data underline the fact that the clinical relevance of a marker can only be truly assessed if studies with similar questions are compared: a useful diagnostic marker might be a useless prognostic marker and vice versa.…”
Section: [H1] Biofluid Mirnas In Prostate Cancermentioning
confidence: 93%
“…In a study aimed at testing the diagnostic utility of three specific PCa-associated miRNAs, miR-21, miR-141, and miR-221, Yaman Agaoglu et al (2011) found that miR-21 and miR-221 were elevated in the plasma of men with localized cancer compared with healthy controls. Moreover, these three miRNAs were increased in samples from men with bone metastases compared with men with localized/locally advanced disease, and miR-141 could accurately distinguish between these groups (AUCZ0.755).…”
Section: Circulating Mirnas As Diagnostic Markers Of Pcamentioning
confidence: 99%
“…Like miR-375, miR-141 is elevated in both the circulation of men with PCa and prostate tumors (Mitchell et al 2008, Brase et al 2011, Gonzales et al 2011, Selth et al 2011, Yaman Agaoglu et al 2011, Bryant et al 2012. miR-141 is a member of the miR-200 family, which functions to repress the epithelial to mesenchymal transition (EMT) by targeting the ZEB family of transcription factors (Bracken et al 2009).…”
Section: Beyond Biomarkers: the Role Of Circulating Mirnas In Pcamentioning
confidence: 99%